A Metal-Free, Nonconjugated Polymer for Solar Photocatalysis - Pino-Lopez, E (Wiley-VCH Verlag, 2017)
Heterogeneous catalysts that can absorb light over the solar range are ideal for green photocatalysis. Recently, attention has been directed towards the generation of novel solar-light photocatalysts, in particular, metal-free polymers. Herein, it is demonstrated that a metal-free, nonconjugated, anthraquinone-based copolymer (poly[1,4-diamine-9,10-dioxoanthracene-alt-(benzene-1,4-dioic acid)] (COP)) with a strong absorption in the visible region is effective as a sunlight heterogeneous photocatalyst. As a proof of concept, it has been used to mineralize 2,5-dichlorophenol (2,5-DCP) in water under air and sunlight irradiation. The photocatalytic efficiency of COP compares well with that of TiO2-P25 when the reaction is carried out in a solar photoreactor in acid medium. Steady-state and time-resolved (absorption and emission) studies performed on COP suspended in 6:4 DMF/H2O have provided valuable information about the COP species generated under different pH conditions. Steady-state absorption and fluorescence data are consistent with the existence of a tautomeric equilibrium between the 9,10-keto and 1,10-iminoketo quinoid forms for the anthraquinone in the ground state. Moreover, in basic media, transient absorption measurements showed the presence of two bands ascribed to the tautomeric triplet excited states, whereas only one of the triplets was observed in acid medium. A mechanism for the photocatalyzed degradation of 2,5-DCP by COP is proposed on the basis of these observations. © 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim